Nonlinear Four-point Impulsive Fractional Differential Equations with p-Laplacian Operator - Fen, Fatma Tokmak; Karaca, Ilkay Yaslan (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we investigate the existence of solutions for a four-point nonlocal boundary value problem of nonlinear impulsive differential equations of fractional order α ∈ (2,3]. By using some well known fixed point theorems, sufficient conditions for the existence of solutions are established. Some illustrative examples are also discussed.